Measuring the Relative Reactivity of the Carbon–Hydrogen Bonds of Alkanes as Nucleophiles. (23rd August 2018) - Olmos, Andrea; Gava, Riccardo; Noverges, Bárbara; Bellezza, Delia; Jacob, Kane; Besora, Maria; Sameera, W. M. Chamil; Etienne, Michel; Maseras, Feliu; Asensio, Gregorio; Caballero, Ana; Pérez, Pedro J.
Abstract: We report quantitative measurements of the relative reactivities of a series of C−H bonds of gaseous or liquid C n H2 n +2 alkanes ( n =1–8, 29 different C−H bonds) towards in situ generated electrophiles (copper, silver, and rhodium carbenes), with methane as the reference. This strategy surpasses the drawback of previous model reactions of alkanes with strong electrophiles suffering from C−C cleavage processes, which precluded direct comparison of the relative reactivities of alkane C−H bonds.